Co-culture of STRO1 + human gingival mesenchymal stem cells and human umbilical vein endothelial cells in 3D spheroids: enhanced in vitro osteogenic and angiogenic capacities - Liu, Yushan; Chen, Pei; Zhou, Tengfei; Zeng, Jincheng; Liu, Ziyi; Wang, Ruijie; Xu, Yiwei; Yin, Wuwei; Rong, Mingdeng (Frontiers in Cell and Developmental Biology, 2024)
Stem cell spheroid is a promising graft substitute for bone tissue engineering. Spheroids obtained by 3D culture of STRO1+ Gingival Mesenchymal Stem Cells (sGMSCs) (sGMSC spheroids, GS) seldom express angiogenic factors, limiting their angiogenic differentiation in vivo. This study introduced a novel stem cell spheroid with osteogenic and angiogenic potential through 3D co-culture of sGMSCs and Human Umbilical Vein Endothelial Cells (HUVECs) (sGMSC/HUVEC spheroids, GHS). GHS with varying seeding ratios of sGMSCs to HUVECs (GHR) were developed. Cell fusion within the GHS system was observed via immunofluorescence. Calcein-AM/PI staining and chemiluminescence assay indicated cellular viability within the GHS. Furthermore, osteogenic and angiogenic markers, including ALP, OCN, RUNX2, CD31, and VEGFA, were quantified and compared with the control group comprising solely of sGMSCs (GS). Incorporating HUVECs into GHS extended cell viability and stability, initiated the expression of angiogenic factors CD31 and VEGFA, and upregulated the expression of osteogenic factors ALP, OCN, and RUNX2, especially when GHS with a GHR of 1:1. Taken together, GHS, derived from the 3D co-culture of sGMSCs and HUVECs, enhanced osteogenic and angiogenic capacities in vitro, extending the application of cell therapy in bone tissue engineering.